2021
DOI: 10.1002/ccr3.4270
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac sarcoidosis: Two case reports

Abstract: The clinical presentation of cardiac sarcoidosis is variable. We report two cases of cardiac sarcoidosis to highlight the varied clinical presentations and diagnostic challenges in our setting, and encourage the consideration of sarcoidosis as a differential in unexplained arrhythmias and heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 37 publications
(59 reference statements)
1
8
0
Order By: Relevance
“…Clinical features of CS depend on the location, extent, and activity of the disease [ 2 ]. Variations of the clinical manifestations include conduction abnormalities, ventricular arrhythmias, sudden death, or new-onset or worsening heart failure [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Clinical features of CS depend on the location, extent, and activity of the disease [ 2 ]. Variations of the clinical manifestations include conduction abnormalities, ventricular arrhythmias, sudden death, or new-onset or worsening heart failure [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conduction abnormalities are the most common manifestations of CS with a prevalence of about 62%. Complete heart blocks and bundle branch blocks are seen in about 23-30% and 12-32%, respectively [ 3 ]. This was evident in our case in which the patient developed intermittent complete heart block and an initial bifascicular block which involved an RBBB, which is usually more common in CS than a left bundle branch block [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data on the disease burden of sarcoidosis in Ghana is not readily available. However, a number of cases have been reported such as that by Bajantri et al who reported on a 53-year-old woman with neurosarcoidosis [ 4 ] and two cases of cardiac sarcoidosis in a 51-year-old man and a 58-year-old woman reported by Afriyie-Mensah et al [ 5 ]. It is more common in females [ 1 ], and the age at diagnosis is usually between 40 and 55 years [ 1 ].…”
Section: Introductionmentioning
confidence: 99%